PENGARUH AKTIVITAS MONTESSORI TERHADAP KEMAMPUAN KOGNITIF KLIEN PSIKOGERIATRI DENGAN SCHIZOFRENIA KRONIS - Suyanta, Suyanta; Hastuti, Tulus Puji; Rahmawati , Wiwin Reny (Jurnal Ilmiah Keperawatan IMELDA, 2024)
Elderly individuals who have been exposed to psychosis (schizophrenia) since youth or adulthood will experience severe cognitive function decline, such as memory deficits, executive function, and attention. Other cognitive functions are also affected, including language function, intelligence, and orientation. Montessori activities are activities that are tailored to the interests and skills of clients and can be applied to stimulate or prevent cognitive decline in the elderly. This study aims to determine the effect of Montessori activities on the cognitive abilities of chronic schizophrenic psychogeriatric clients. The research design is a quasi-experimental study with a non-randomized control group pre-post test design. Data collection used the MMSE (Mini Mental State Examination) questionnaire or Folstein test twice, before and after the intervention. The sample size was 30 people, divided into 15 people in the experimental group and 15 people in the control group. The research was conducted at the Laras Jiwo Psychiatric Rehabilitation Center in the Magelang Regency area from September to November 2022. The results showed that Montessori activities did not significantly affect the improvement of cognitive abilities (MMSE score), as evidenced by the Mann-Whitney test results with the difference coefficient of the posttest between the experimental and control groups obtained a z-value of -1.579 and a p-value of 0.114 (p>0.05). However, the difference coefficient between pre and post in the experimental group showed a significant difference with a z-value of -3.436 and a p-value of 0.001 (p<0.05), thus it can be concluded that Montessori activities still have an effect on improving MMSE in the experimental group.